Towards a phylogenetic classification of species belonging to the diatom genus Cyclotella (Bacillariophyceae): Transfer of species formerly placed in Puncticulata, Handmannia, Pliocaenicus and Cyclotella to the genus Lindavia - Nakov, Teofil; Guillory, Wilson; Julius, Matthew; Theriot, Edward; Alverson, Andrew (Phytotaxa, 2015)
Cyclotella is a commonly encountered name in the diatom literature. The name is attached, however, to a historically vaguely defined and polyphyletic genus whose taxonomy and systematics remain muddled despite numerous taxonomic treatments. One recent chapter in this history concerns species informally known as the “Cyclotella comta” group, which have one or more rimoportulae on the valve face. These species were grouped into a new genus, Puncticulata, a name that has been applied inconsistently since its introduction. The name Puncticulata eventually was shown to be illegitimate, as some species had once been classified within Handmannia, which had nomenclatural priority. An inventory of names within Cyclotella sensu lato revealed that both Puncticulata and Handmannia are later synonyms of Lindavia. We identify a rimoportula positioned on the valve face as a synapomorphy for a group of taxa with the Cyclotella comta and C. ocellata bauplans (including Pliocaenicus), and accordingly, we transfer taxa with this synapomorphy into the genus Lindavia.